On the Effects of Br−, Clo4−, No3−Anions on the Oxygen Reduction Reaction Electrocatalysis at Fe Phthalocyanine Modified Electrodes - Tasca-Gottardo, F; Tasca-Gottardo, F; Zúñiga-Loyola, C; Zúñiga-Loyola, C (Elsevier Ltd, 2024)
Fe phthalocyanine with carbon nanotubes (FePc-CNT) has been used as catalysts for ORR using the following supporting electrolyte: 0.1 M NaOH, 1 M NaOH, 1 M HNO3, 1 M HClO4, and 1 M HBr. The thermodynamic and kinetic information was acquired from cyclic voltammetry in N2 saturated media, and then polarization curves saturating with O2. The rate-determining step is modulated by the formal potential (E0’Fe(III)/(II)) in basic media, coherent with the inner sphere electron transfer mechanism. However, in strong acid electrolytes, the Tafel slope value is ∼ -0.090 V dec−1 at low overpotentials and ∼ -0.120 V dec−1 at high overpotentials indicating that a poisoning process is hampering the ORR, and causing an outer sphere electron transfer mechanism. Impedance spectroscopy and poisoning test (recovery of the activity of the catalyst in NaOH after initial use in acid) support the thesis of ion adsorption/poisoning for the low electrocatalytic activity of FePc based catalysts in acid media. © 2023